2018
DOI: 10.1007/s00784-018-2437-7
|View full text |Cite
|
Sign up to set email alerts
|

Compromised alveolar bone cells in a patient with dentinogenesis imperfecta caused by DSPP mutation

Abstract: DSPP mutation can induce the behavior alterations of alveolar bone cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…Dentin sialophosphoprotein was initially found to be specifically expressed by odontoblasts and transiently by pre-ameloblasts ( D’Souza et al, 1992 ; Begue-Kirn et al, 1998 ), while it was later observed also in bone ( Qin et al, 2002 ), periodontium ( Baba et al, 2004 ) and other non-mineralized tissues ( Ogbureke and Fisher, 2004 , 2007 ; Sun et al, 2010 ; Prasad et al, 2011 ). Patients with DGI have compromised alveolar bone cells ( Porntaveetus et al, 2019 ), suggesting that these patients may suffer from periodontal diseases. DGI-III animal model ( Dspp null mice) developed severe periodontitis, also displayed impaired cranial bone development and long bone mineralization ( Verdelis et al, 2008 ; Gibson et al, 2013b ; Chen et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dentin sialophosphoprotein was initially found to be specifically expressed by odontoblasts and transiently by pre-ameloblasts ( D’Souza et al, 1992 ; Begue-Kirn et al, 1998 ), while it was later observed also in bone ( Qin et al, 2002 ), periodontium ( Baba et al, 2004 ) and other non-mineralized tissues ( Ogbureke and Fisher, 2004 , 2007 ; Sun et al, 2010 ; Prasad et al, 2011 ). Patients with DGI have compromised alveolar bone cells ( Porntaveetus et al, 2019 ), suggesting that these patients may suffer from periodontal diseases. DGI-III animal model ( Dspp null mice) developed severe periodontitis, also displayed impaired cranial bone development and long bone mineralization ( Verdelis et al, 2008 ; Gibson et al, 2013b ; Chen et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…To this end, we performed ALP and ARS staining to monitor ALP activity and mineralization, respectively, and we examined the levels of expression of odontoblastic differentiation markers DSPP, BSP, ALP and OPN. DSPP is the primary noncollagenous protein in tooth dentin and has long been regarded as a specific marker of dentinogenesis [24]. BSP is an acidic noncollagenous glycoprotein abundantly expressed in mineralized tissues and performs an essential function in the initial mineralization of bone, dentin and cementum [25].…”
Section: Discussionmentioning
confidence: 99%
“…Patients consulted for diagnosis by NGS are from all specialties, including neurologists (Veeravigrom et al, ), dentists (Intarak, Theerapanon, Ittiwut, et al, ; Nowwarote et al, ; Porntaveetus, Nowwarote, et al, b; Porntaveetus, Osathanon, et al, ), orthopedists, endocrinologists (Sangsin, Srichomthong, Pongpanich, Suphapeetiporn, & Shotelersuk, , ), hematologists (Ittiwut et al, ; Ittiwut et al, ), dermatologists (Intarak, Theerapanon, Srijunbarl, et al, ; Panmontha et al, ; Panmontha et al, ), immunologists (Suratannon et al, ), syndromologists (Porntaveetus, Abid, et al, ; Porntaveetus, Srichomthong, Ohazama, Suphapeetiporn, & Shotelersuk, ; Porntaveetus, Theerapanon, Srichomthong, & Shotelersuk, ), biochemical geneticists (Chaiyasap et al, ; Phowthongkum, Ittiwut, & Shotelersuk, ; Porntaveetus, Srichomthong, Suphapeetiporn, & Shotelersuk, ), oncologists (Sahakitrungruang et al, ), and radiologists (Yeetong, Phewplung, Kamolvisit, Suphapeetiporn, & Shotelersuk, ). We have observed a wide range of yields depending on disease groups, recruitment criteria and, very importantly the cooperation of the clinicians and the bioinformaticians.…”
Section: Rare and Undiagnosed Diseasesmentioning
confidence: 99%